2017
DOI: 10.1590/s1984-29612017030
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia canis and Rickettsia spp. in dogs from urban areas in Paraiba state, northeastern Brazil

Abstract: The aims of our study was to identify Ehrlichia canis and antibodies against Rickettsia spp. belonging to the spotted fever group (SFG) in dogs sampled from Paraiba state, northeastern Brazil. Blood and serum samples collected by convenience from dogs in urban areas of five municipalities were analyzed by real-time PCR for the detection of E. canis DNA and by immunofluorescence assay test (IFAT) for the identification of antibodies against Rickettsia rickettsii, R. felis, R. parkeri, R. amblyommii and R. rhipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
9
1
Order By: Relevance
“…These results contribute to determining the negative relationship between feral dogs and wild animals of REPSA regarding disease transmission. Ehrlichia canis (the causative agent of canine monocytic ehrlichiosis) is the main rickettsial agent registered in dogs of the Neotropical region, with prevalence ranging between 15 and 70% (BARRANTES-GONZÁLEZ et al, 2016;MONTENEGRO et al, 2017;ROTONDANO et al, 2017;GEIGER et al, 2018;PAULINO et al, 2018). Clinical signs of an E. canis infection can be variable, depending on the strain, the immune response of the dog, and the presence of concomitant infections with other tick or flea-borne pathogens (SAINZ et al, 2015), however, no clinical signs were observed in the animals captured.…”
Section: Discussionmentioning
confidence: 99%
“…These results contribute to determining the negative relationship between feral dogs and wild animals of REPSA regarding disease transmission. Ehrlichia canis (the causative agent of canine monocytic ehrlichiosis) is the main rickettsial agent registered in dogs of the Neotropical region, with prevalence ranging between 15 and 70% (BARRANTES-GONZÁLEZ et al, 2016;MONTENEGRO et al, 2017;ROTONDANO et al, 2017;GEIGER et al, 2018;PAULINO et al, 2018). Clinical signs of an E. canis infection can be variable, depending on the strain, the immune response of the dog, and the presence of concomitant infections with other tick or flea-borne pathogens (SAINZ et al, 2015), however, no clinical signs were observed in the animals captured.…”
Section: Discussionmentioning
confidence: 99%
“…Since E. canis was first detected in Algeria in 1935, it has been found in dogs and ticks in North America, Europe, Asia, and Africa. At present, CME is spreading all over the world [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of infection by E. canis in the canine population of Vila de Jericoacoara was similar to that found in other studies conducted in the northeastern region of Brazil. Rotondano et al (2017) found the molecular occurrence of E. canis 8.9% among dogs in an urban area in the state of Paraíba. In this region of Brazil, the molecular ocurrence of E. canis infection has ranged from 1.7% to 25% (Tanikawa et al, 2013;Costa et al, 2015;Rotondano et al, 2015Rotondano et al, , 2017Dantas-Torres et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…antibodies. Although these pathogens had previously been reported infecting dogs in other states in Brazil (Saito et al, 2008;Ramos et al, 2010;Spolidorio et al, 2011;Vieira et al, 2011;Costa et al, 2015; Tick-borne pathogens in dogs in Ceará, Brazil Miranda et al, 2014;Rotondano et al, 2015Rotondano et al, , 2017Lopes et al, 2019;Oliveira et al, 2020), data relating to Ceará were very scarce, and were mainly from the coastal region. Recently, R. rickettsii, R. amblyommatis and E. canis were reported infecting dogs in the National Forest (FLONA) of Araripe-Apodi, in the municipality of Crato, state of Ceará (Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%